The damage and remineralization strategies of dental hard tissues following radiotherapy - Lin Yao; Yanyao Li; Di Fu; Ye Wang; Chengge Hua; Ling Zou; Li Jiang (BMC, 2024)
Abstract Objectives This study pursued two main purposes. The first aim was to expound on the microscopic factors of radiation-related caries (RRC). Further, it aimed to compare the remineralization effect of different remineralizing agents on demineralized teeth after radiotherapy. Methods The enamel and dentin samples of bovine teeth were irradiated with different doses of radiation. After analysis of scanning electron microscope (SEM), X-Ray diffraction (XRD), and energy dispersive spectrometer (EDS), the samples irradiated with 50 Gy radiation were selected and divided into the demineralization group, the double distilled water (DDW) group, the Sodium fluoride (NaF) group, the Casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) group, the NaF + CPP-ACP group, and the Titanium tetrafluoride (TiF4) group. After demineralization, remineralizing agents treatment, and remineralization, the samples were evaluated using SEM, atomic force microscope (AFM), EDS, and transverse microradiography (TMR). Results A radiation dose of 30 Gy was sufficient to cause damage to the dentinal tubules, but 70 Gy radiation had little effect on the microstructure of enamel. Additionally, the NaF + CPP-ACP group and the TiF4 group significantly promoted deposit formation, decreased surface roughness, and reduced mineral loss and lesion depth of demineralized enamel and dentin samples after radiation. Conclusions Radiation causes more significant damage to dentin compared to enamel. NaF + CPP-ACP and TiF4 had a promising ability to promote remineralization of irradiated dental hard tissues. Advances in knowledge This in vitro study contributes to determining a safer radiation dose range for teeth and identifying the most effective remineralization approach for RRC.